2009
DOI: 10.1136/gut.2009.176651
|View full text |Cite
|
Sign up to set email alerts
|

Super paramagnetic iron oxide MRI shows defective Kupffer cell uptake function in non-alcoholic fatty liver disease

Abstract: KC uptake function is significantly impaired in patients with NAFLD and experimental animals with NASH, worsens with the degree of steatosis and is not due to a reduction of KC numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 32 publications
9
56
2
2
Order By: Relevance
“…Namely, it has been considered to represent the phagocytic activity of KCs. However, recent studies have reported that impairment of KC phagocytic activity is dependent on the level of activity in each KC and is not dependent on a reduction in the total number of KCs in studies of animal models of non-alcoholic steatohepatitis (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…Namely, it has been considered to represent the phagocytic activity of KCs. However, recent studies have reported that impairment of KC phagocytic activity is dependent on the level of activity in each KC and is not dependent on a reduction in the total number of KCs in studies of animal models of non-alcoholic steatohepatitis (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…17 In contrast to USPIO, SPIONs are characterized by enhanced liver accumulation, thereby constituting a superb hepatic MRI contrast agent. Low concentrations of SPIONs (0.5 mg Fe/kg of carboxydextran-coated ferucarbotran (Resovist/Ferrixan, 45-60 nm [18][19][20], or dextran-coated ferumoxides (Endorem/Feridex), 21 have been used to noninvasively distinguish between benign liver condition (simple steatosis) and nonalcoholic steatohepatitis (NASH), which is highly associated with cardiovascular and renal comorbidities. 22 Despite promising results in humans, the marketing of intravenous iron oxide-containing contrast agents is currently at a standstill.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that K-604 inhibited ACAT-1 and thus modulated the cholesterol levels in the Kupffer cells. As previously reported, impaired Kupffer cell function is important in the pathogenesis of NASH [29][30][31]. Thus, within the paradigm of the NASH etiology, it appears plausible that the inhibition of ACAT-1 by K-604 may suppress foam cell formation and lead to the normalized phagocytic function and morphology of the Kupffer cells.…”
Section: Body Weights Plasma Profiles Plasma Concentrations Of K-60mentioning
confidence: 60%